Philosophy and politics in the thought of John Wyclif - Lahey, Stephen E. (Cambridge University Press, 2003)
John Wyclif was the fourteenth-century English thinker responsible for the first English Bible, and for the Lollard movement. In contrast with most other commentaries, this book argues that Wyclif's political programme was based on a coherent philosophical vision ultimately consistent with his earlier reformative ideas.
Keywords: Wycliffe, John, -- -1384 -- Contributions in doctrine of church and state.; Wycliffe, John, -- -1384.; Wycliffe, John, -- -1384; Wyclif, John.; Church and state -- England -- History -- To 1500.; RELIGION -- Christian Church -- History.; RELIGION -- Christianity -- History.; Church and state; England; Politische Philosophie; Politieke filosofie.; To 1500; History